X-ray radiation during pulsed laser treatment of opal matrices - Belyanin, A.F.; Borisov, V.V.; Popov, V.V. (Технология и конструирование в электронной аппаратуре, 2018)
The paper presents the structure and preparation conditions of opal matrices (ordered 3D-lattice packing of X-ray amorphous SiO2 spheres with a diameter of ≈250 nm), as well as experimental data on nonlinear optical effects in opal matrices with pulsed laser excitation at wavelengths: 1040 nm, 510 nm in conjunction with 578 nm, and 366 nm. The authors investigate the energy spectra of X-ray radiation induced in the samples by laser irradiation. В настоящей работе представлены результаты исследования с помощью рентгеновского спектрометра энергетических спектров рентгеновского излучения, индуцированного воздействием на опаловые матрицы импульсного лазерного излучения с различной длиной волны λ: 1040 нм (ИК-область спектра), 510 и 578 нм (совмещенные моды) и 366 нм (УФ-область). У даній роботі представлено результати вимірювання за допомогою рентгенівського спектрометра енергетичних спектрів рентгенівського випромінювання, індукованого впливом на ОМ імпульсного лазерного випромінювання з різною довжиною хвилі λ: 1040 нм (ІЧ-область спектра), 510 та 578 нм (суміщенні моди), 366 нм (УФ-область).